Eco-friendly preparation of zinc oxide nanoparticles and effects on Staphylococcus aureus isolated from subclinical mastitis cow milk - Bozkurt, MA; Keyvan, E; Donmez, S; Sen, E (Journal of the Hellenic Veterinary Medical Society, 2024)
The study aimed to investigate the eco-friendly preparation of zinc oxide nanoparticles (ZnO NPs) using Origanum minutiflorum extract and the inactivation effect of the ZnO NPs to isolates from subclinical mastitis cow milk. The ZnO NPs were found to peak at around 350 nm in the UV-Visible analysis. The ZnO NPs were imaged using scanning electron microscopy (SEM) to confirm their uniform distribution and nano-sized range. The average crystallite size was 15.86 nm. By scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radicals, green synthesized ZnO NPs showed antioxidant activity. In a consequence of the evaluation for subclinical mastitis, 144 (41.14%) of the dairy animals were positive. Thirty-four isolates (14.70%) were identified as Staphylococcus aureus by PCR, and 29 (20.13%) of the dairy animals with subclinical mastitis were also found to be S. aureus positive. Antibiotic resistance was observed in the isolates. Origanum minutiflorum-mediated ZnO NPs have been found to have antibacterial activity against all isolates, with minimum inhibitory concentration (MIC) values ranging from 2.5 to 2000 µg/mL. In conclusion, an alternative antibacterial product synthesis has been provided for antibiotic substances. Because of the rising incidence of antibiotic resistance in isolates, more research on antibiotic alternatives needs to be considered.